Morphological and Molecular Characteristics of Pratylenchus coffeae from the Origin of Robusta Coffee Plantation in Malang, East Java - Aris Budiman; Supramana Supramana; Giyanto Giyanto (Jurnal Perlindungan Tanaman Indonesia, 2019)
Pratylenchus coffeae is the most important plant-parasitic nematode in Robusta coffee plantations. Information regarding morphology, morphometric and molecular characters of P. coffeae has not been reported in Indonesia. This study is aimed to describe those characters of P. coffeae that attack Robusta coffee. Root samples were taken from Robusta coffee plantation in Malang, East Java. Nematode extractions was conducted using a mist chamber method. Morphology and morphometric characters were observed from the permanent nematode slides. Single nematode DNA extract was amplified at the D2D3 segment of 28S rRNA and ITS1-5.8S-ITS2 rRNA with universal primers. Amplicon was sequenced and analysed for phylogenetic tree relationships. Female morphological key character of P. coffeae observed are: lip with two annulations, four lateral lines, esophageal overlap with intestine ventrally, monodelphic, and truncated tail shape. Male spicules curved ventrally. Female morphometrics are: n=26, L = 556.4 μm, DGO = 2.4 μm, anterior gonad = 174.8 μm, a = 28.5, b = 6.1, b’ = 4.1, c = 20.1, c’ = 2.3, V = 81.7. A Male is smaller than a female with n=24, L = 505.9 μm,  a = 32.3, b = 5.5, b '= 3.9, c = 15.3, c' = 2.8 and T = 40.6. The molecular characters of P. coffeae were investigated for two isolates, namely SA1 and SA2.  Based on the D2D3 and ITS1-5.8S-ITS2 regions, isolate SA1 has similarity level of 99% and 97% to the P. coffeae  from NCBI. Similar result was shown by Isolate SA2 with similarity of 100% and 100% respectively. Phylogenetic tree analysis using Maximum Likelihood at the D2D3 segment of 28S rRNA and ITS1-5.8S-ITS2 regions showed that P. coffeae in this study was included in one clade with P. coffeae from several countries.